(untitled) (National Administration Journal, 2025)
The article presents the evolution of the brand of the Distance State University (UNED) of Costa Rica, from its creation in 1977 to the present day, through the review and update processes of the Visual Identity Manual (MIVI) developed by the Institutional Office of Marketing and Communication. During 2024 and 2025, a thorough brand update has been carried out to attract and retain new market segments while strengthening the trust and loyalty of its existing audience. Using a qualitative, exploratory methodology, the historical method was applied to collect information and locate documentary sources in order to understand the decisions that have shaped the evolution of UNED’s distinctive identity and to develop strategies for brand renewal. The process concludes that emotional marketing has predominantly prevailed, prioritizing people’s sense of identification and belonging.